2022
DOI: 10.1007/s12020-022-03050-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating irisin levels in functional hypothalamic amenorrhea: a new bone damage index? A pilot study

Abstract: Purpose Patients with functional hypothalamic amenorrhea (FHA) could commonly have bone damage, often preceded by metabolic alterations due to a relative energy deficit state. To date, there are no markers capable of predicting osteopenia before it is manifested on DXA. Irisin is a myokine that promotes the differentiation of osteoblastic cells and appears to be inversely correlated with the incidence of bone fragility and fractures in postmenopausal women. The aim of this study was to measure ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Irisin levels were positively associated with metrics of BMD and bone strength and structure in both athletes across all groups [96]. A more recent study revisited the subject of irisin changes in FHA, removing the factor of physical exercise [99]. Patients with FHA displayed significantly lower BMIs and irisin concentrations when compared to healthy aged-matched controls associated with lower BMDs, which, however, did not reach the osteopenic range [99].…”
Section: Irisin In Hypothalamic Amenorrheamentioning
confidence: 97%
See 1 more Smart Citation
“…Irisin levels were positively associated with metrics of BMD and bone strength and structure in both athletes across all groups [96]. A more recent study revisited the subject of irisin changes in FHA, removing the factor of physical exercise [99]. Patients with FHA displayed significantly lower BMIs and irisin concentrations when compared to healthy aged-matched controls associated with lower BMDs, which, however, did not reach the osteopenic range [99].…”
Section: Irisin In Hypothalamic Amenorrheamentioning
confidence: 97%
“…A more recent study revisited the subject of irisin changes in FHA, removing the factor of physical exercise [99]. Patients with FHA displayed significantly lower BMIs and irisin concentrations when compared to healthy aged-matched controls associated with lower BMDs, which, however, did not reach the osteopenic range [99]. Of note, a similar decrease in irisin levels has not been reported in the context of anorexia nervosa (AN), which appears counterintuitive.…”
Section: Irisin In Hypothalamic Amenorrheamentioning
confidence: 99%
“…Another study showed lower irisin levels in non-athletes and non-anorexic women with FHA, compared to healthy controls [70]. The authors considered physical exercise and eating disorders as confounding factors because they influence serum irisin levels independently, and decided to focus on patients with FHA due to psychogenic stress.…”
Section: Irisin and Functional Hypothalamic Amenorrheamentioning
confidence: 99%
“…The FHA group showed lower irisin levels associated with significantly reduced BMD parameters that did not reach the severity of osteopenia. Therefore, the authors hypothesized that irisin could predict DXA outcomes and, in turn, irisin measurement could allow earlier targeted therapies, to avoid osteoporosis [70].…”
Section: Irisin and Functional Hypothalamic Amenorrheamentioning
confidence: 99%
“…Exercise activates PGC-1α, up-regulating FNDC5/Irisin and reducing amyloid-beta (Aβ) production [74,75]. Irisin levels rise in response to exercise, potentially improving cognitive functions via various mechanisms, including promoting neuronal growth and reducing inflammation [76][77][78][79][80][81][82][83][84][85][86][87][88][89]. Irisin also influences the production of BDNF, a factor crucial for neuronal health [90][91][92].…”
mentioning
confidence: 99%